2012
DOI: 10.1080/08873267.2012.643692
|View full text |Cite
|
Sign up to set email alerts
|

Occluded humanistic qualitative research: Implications for positive psychology.

Abstract: A reply is given to the charge made by the originators of the current positive psychology movement that humanistic psychology has not provided an adequate empirical base for its positive psychology. It is observed that although it is more about ontology, or the nature of being, than a scientific field as such, there is an extensive body of empirical qualitative research pertinent to humanistic psychology, including the positive psychology it originated. It is argued that the visibility of this research has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Thus, the two-interview approach used by Camiré (2016) was replicated with the emphasis placed on getting the athlete to share the meaning he attributed to his developmental experiences over the course of his career. Throughout the research process, the main researcher embraced a humanistic approach (Rennie, 2012), which guided the decisions he made pre-interview (e.g., framing interview questions in a non-judgmental manner), during interview (e.g., genuinely empathizing with the athlete as he cried for a moment while vividly remembering the death of his mother), and post-interview (researcher and athlete jointly reflecting on the researchers' interpretations). Using the humanistic approach (Rennie, 2012), the main researcher was able to develop strong rapport with the athlete who felt comfortable expressing his opinions and emotions related to the successes (e.g., winning…”
Section: Interviewsmentioning
confidence: 99%
“…Thus, the two-interview approach used by Camiré (2016) was replicated with the emphasis placed on getting the athlete to share the meaning he attributed to his developmental experiences over the course of his career. Throughout the research process, the main researcher embraced a humanistic approach (Rennie, 2012), which guided the decisions he made pre-interview (e.g., framing interview questions in a non-judgmental manner), during interview (e.g., genuinely empathizing with the athlete as he cried for a moment while vividly remembering the death of his mother), and post-interview (researcher and athlete jointly reflecting on the researchers' interpretations). Using the humanistic approach (Rennie, 2012), the main researcher was able to develop strong rapport with the athlete who felt comfortable expressing his opinions and emotions related to the successes (e.g., winning…”
Section: Interviewsmentioning
confidence: 99%
“…A different strand of critique, as voiced by Rennie (2012) has suggested that positive psychology is not really a separate discipline but could be seen as part of humanistic psychology, and he observes that positive psychology has sought to dissociate itself from humanistic psychology mainly for methodological reasons, which Rennie suggests are illfounded due to the strong empirical traditions within humanistic psychology that may have been overlooked. A reason for this could be that much high-quality research done within humanistic psychology is published in journals not connected with the movement, similar to counseling psychologists in the UK who often publish their work in journals relating to their field of research rather than to their professional discipline, which makes it more difficult to trace back their output.…”
Section: Development and Identity Of Counseling Psychologymentioning
confidence: 99%